Wood powder resin composite material, molding product, method for manufacturing wood powder resin composite material and method for manufacturing molding product

By controlling acetic acid content in steamed wood flour and using a resin with a compatibilizer, the composite material achieves odor resistance and maintains mechanical properties, addressing the odor issue in wood-based composites.

JP2025005208APending Publication Date: 2025-01-16RIYOUKA SANGYO
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023105295
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-27
Publication Date
2025-01-16

AI Technical Summary

Technical Problem

Wood-based materials treated with steam generate strong odors due to chemical reactions, limiting the usage of molded products made from wood-based composite materials.

Method used

Control the content of acetic acid in steamed wood flour by adjusting the peak height ratio to 0.1 or less relative to carbon dioxide using gas chromatography mass spectrometry, and incorporate a resin with a compatibilizer to create a wood powder resin composite material.

Benefits of technology

The resulting composite material exhibits excellent odor resistance and maintains mechanical properties such as tensile strength, bending strength, and impact strength, while ensuring moldability and environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025005208000003
    Figure 2025005208000003
  • Figure 2025005208000004
    Figure 2025005208000004
  • Figure 2025005208000001
    Figure 2025005208000001
Patent Text Reader

Abstract

To provide wood powder resin composite materials with excellent odour resistance.SOLUTION: A wood powder resin composite material comprises steamed wood powder and resin, and the steamed wood power has a ratio of a peak height of acetic acid identified by total ion chromatogram obtained by gas chromatography mass spectrometry to a peak height of carbon dioxide identified by the total ion chromatogram of 0.1 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a wood flour resin composite material, a molded product, a method for producing a wood flour resin composite material, and a method for producing a molded product. [Background technology]

[0002] The technology for compounding wood flour and plastic has a history of more than 30 years, and research is being conducted to increase the wood ratio in wood flour and plastic composites due to growing environmental awareness, etc. Specifically, research is being conducted on improving the compatibility between wood flour and plastic, which has low compatibility, and on pre-treatment of wood flour before compounding in order to prevent loss of the moldability and mechanical properties of plastic.

[0003] For example, Patent Document 1 discloses a lignocellulose-based thermoplastic material obtained by steam-treating a lignocellulose-containing material with the aim of providing a new thermoplastic material made from a lignocellulose-containing material, and discloses that the lignocellulose-based thermoplastic material can be used in combination with a conventional thermoplastic resin material. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2003-165844 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, when wood-based materials are treated with steam, the wood decomposes and the components in the wood react chemically to generate multiple odorous components. As a result, when composite materials are produced and molded using such steamed wood-based materials, the molded products have a strong odor, limiting their uses. Therefore, wood flour resin composite materials, which are made by combining wood flour and resin, the raw materials for such molded products, are required to have excellent odor resistance and suppress odor generation.

[0006] Therefore, the present invention has been made in consideration of the above problems, and an object of the present invention is to provide a wood flour resin composite material that has excellent odor resistance. [Means for solving the problem]

[0007] As a result of intensive research into achieving the above-mentioned object, the inventors discovered that the main cause of the odor in wood flour to be steamed and cooked is acetic acid produced by the application of heat, and that the above-mentioned problem can be solved by controlling the content of acetic acid in the wood flour to be steamed and cooked, thereby completing the present invention.

[0008] That is, the present invention is as follows. [1] Steamed wood flour, A resin, The wood flour to be steamed and cooked has a ratio of the peak height of acetic acid identified by a total ion chromatogram obtained by gas chromatography-mass spectrometry to the peak height of carbon dioxide identified by the total ion chromatogram, which is 0.1 or less; Wood powder resin composite. [2] The steamed wood flour has a ratio of the peak height of acetic acid, formaldehyde, and acetaldehyde identified by a total ion chromatogram obtained by gas chromatography-mass spectrometry to the peak height of carbon dioxide identified by the total ion chromatogram, which is 0.1 or less. [1] A wood powder resin composite material. [3] Further comprising a compatibilizer, [1] A wood powder resin composite material. [4] The content of the steamed wood flour is more than 50% by mass with respect to the total amount of the wood flour resin composite. The wood flour resin composite material according to any one of [1] to [3]. [5] [1] to [4] are obtained by molding the wood powder resin composite material. Molded product. [6] The thickness is 1.2 mm or less. [5] A molded product as described in the above. [7] A steaming process in which wood flour is steamed to obtain a steamed wood flour; A washing step of washing the steamed and cooked wood flour; A mixing step of mixing the steamed wood flour that has been subjected to the washing step with a resin to obtain a wood flour resin composite material, The ratio of the peak height of acetic acid identified by a total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour after the washing step to the peak height of carbon dioxide identified by a total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour before the washing step is 0.1 or less. A method for manufacturing wood flour resin composite materials. [8] The ratio of the peak height of acetic acid, formaldehyde, and acetaldehyde identified by a total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour after the washing step to the peak height of carbon dioxide identified by a total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour before the washing step is 0.1 or less. A method for producing a wood powder resin composite material according to [7]. [9] [7] or [8], comprising a molding step of molding the wood powder resin composite obtained by the method for producing a wood powder resin composite according to the present invention to obtain a molded product; Manufacturing method for molded products.

[10] The molding temperature in the molding step is 160° C. or higher and 180° C. or lower. A method for producing the molded product described in [9].

[11] The mold temperature in the molding step is 60°C or higher and 85°C or lower. A method for producing a molded product according to

[10] . Effect of the Invention

[0009] According to the present invention, a wood flour resin composite material having excellent odor resistance can be provided. [Brief description of the drawings]

[0010] [Figure 1] Total ion chromatogram obtained by gas chromatography mass spectrometry of the steamed wood flour before the washing process of Example 1 [Diagram 2] Total ion chromatogram obtained by gas chromatography mass spectrometry of the steamed wood flour subjected to the washing process of Example 1 DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] 1.Wood resin composite material The wood flour resin composite of this embodiment includes steamed and cooked wood flour and a resin, and the steamed wood flour has a ratio of the peak height of acetic acid identified in a total ion chromatogram obtained by gas chromatography-mass spectrometry to the peak height of carbon dioxide identified in the total ion chromatogram, which is 0.1 or less.

[0012] Generally, when wood flour and resin are composited, moldability and mechanical properties (strength, toughness, etc.) tend to decrease as the ratio of wood flour increases, so wood flour is subjected to steaming treatment or the like to improve moldability and mechanical properties. Conventionally, odorous components are generated in wood flour by steaming treatment or the like, and the odor level tends to increase as the ratio of wood flour increases. Here, it is known that multiple odorous components such as formaldehyde, formic acid, and acetic acid are generated when wood flour is steamed, but the contribution of each component to the odor has not been clarified.

[0013] On the other hand, in this embodiment, by adjusting the content of acetic acid in the wood flour to be steamed and cooked, it is possible to improve, in particular, the odor of the wood flour resin composite material.

[0014] In other words, the wood flour resin composite of this embodiment, particularly the steamed wood flour, has a ratio of the peak height of acetic acid identified in a total ion chromatogram obtained by gas chromatography-mass spectrometry to the peak height of carbon dioxide identified in the total ion chromatogram, of 0.1 or less, and therefore the wood flour resin composite and its molded products have excellent odor resistance.

[0015] The wood flour resin composite of this embodiment has a tensile strength measured under the following measurement condition A of preferably 25 MPa or more, more preferably 30 MPa or more, and even more preferably 35 MPa or more. When the wood flour resin composite has a tensile strength of 25 MPa or more, the strength of the molded product tends to be even better. The upper limit of the tensile strength is not particularly limited, but may be, for example, 100 MPa or less, or 80 MPa or less. <Measurement condition A> Sample: Dumbbell piece (total length: 170 mm, distance between tabs: 105 mm, length of parallel part: 85 mm, width of end: 20 mm, width of central parallel part: 10 mm, thickness: 4.0 mm) Test room temperature: 23±2℃ Test humidity: 50±5%RH Conditioning: 88+ hours in laboratory Testing machine: Autograph AG-100kNXPlus (manufactured by Shimadzu Corporation) Load cell capacity: 5kN Extensometer: TRViewX500D (Shimadzu Corporation) Distance between gauge lines: 75mm Distance between grips: 115mm Test speed: 50mm / min

[0016] The wood flour resin composite of this embodiment has a bending strength measured under the following measurement condition B of preferably 50 MPa or more, more preferably 55 MPa or more, and even more preferably 60 MPa or more. When the wood flour resin composite has a bending strength of 50 MPa or more, the strength of the molded product tends to be even better. The upper limit of the bending strength is not particularly limited, but may be, for example, 100 MPa or less, or 80 MPa or less. <Measurement condition B> Sample: Dumbbell piece (total length: 170 mm, distance between tabs: 105 mm, length of parallel part: 85 mm, width of end: 20 mm, width of central parallel part: 10 mm, thickness: 4.0 mm) Test room temperature: 23±2℃ Test humidity: 50±5%RH Conditioning: 88+ hours in laboratory Testing machine: Autograph AG-10TD (Shimadzu Corporation) Load cell capacity: 5kN Distance between fulcrums: 64mm Support base radius: 5mm Indenter radius: 5mm Test speed: 2mm / min

[0017] The wood powder resin composite material of this embodiment preferably has an impact strength of 1.6 kJ / m2 or less according to a Charpy impact test measured under the following measurement condition C. 2 More preferably, it is 1.8 kJ / m or more. 2 More preferably, it is 2.0 kJ / m 2 The impact strength of the wood powder resin composite material is 1.6 kJ / m or more. 2By setting the impact strength at or above 10 kJ / m, the toughness of the molded product tends to be further improved. The upper limit of the impact strength is not particularly limited, but for example, the impact strength is 10 kJ / m 2 may be less than 8 kJ / m 2 It may be the following. <Measurement conditions C> Sample: Dumbbell piece (total length: 170 mm, distance between tabs: 105 mm, length of parallel part: 85 mm, width of end: 20 mm, width of central parallel part: 10 mm, thickness: 4.0 mm) Test room temperature: 23±2℃ Test humidity: 50±5%RH Conditioning: 88+ hours in laboratory Notch shape: Shape A (angle 45°, notch tip radius 0.25 mm, notch radius 2.8 mm) Testing machine: Digital impact testing machine DG-UB (manufactured by Toyo Seiki Co., Ltd.) Nominal pendulum energy: 1J Impact direction: Edgewise Calculation method for absorbed energy: Simple correction method

[0018] The wood flour resin composite of this embodiment has a deflection temperature under load measured under the following measurement condition D of preferably 140° C. or less, more preferably 120° C. or less, and even more preferably 110° C. or less. When the deflection temperature under load is 140° C. or less, the moldability of the wood flour resin composite tends to be further improved. The lower limit of the deflection temperature under load is not particularly limited, but may be, for example, 80° C. or more, or 90° C. or more. <Measurement condition D> Sample: Dumbbell piece (total length: 170 mm, distance between tabs: 105 mm, length of parallel part: 85 mm, width of end: 20 mm, width of central parallel part: 10 mm, thickness: 4.0 mm) Deflection temperature under load test: JIS K 7191-1:2007 Testing machine: HDT test equipment 6M-2 (manufactured by Toyo Seiki Co., Ltd.) Distance between fulcrums: 64mm Test piece placement: Flatwise Bending stress: 0.45MPa Heating rate: 120℃ / h

[0019] Furthermore, the wood flour resin composite of this embodiment has a deflection temperature under load (°C) measured under measurement conditions E which are the same as measurement conditions D except that the bending stress is changed to 1.80 MPa, of preferably 120°C or less, more preferably 110°C or less, and even more preferably 90°C or less. When the deflection temperature under load is 120°C or less, the moldability of the wood flour resin composite tends to be further improved. The lower limit of the deflection temperature under load is not particularly limited, but may be, for example, 50°C or more, or 60°C or more.

[0020] 1.1.Steamed wood flour The wood flour to be steamed and cooked in this embodiment means wood flour that has been subjected to a steaming treatment. Wood flour means wood that has been crushed and powdered. The upper limit of the particle size range of the wood flour in this embodiment is not particularly limited, but is preferably 1000 μm or less, more preferably 900 μm or less, even more preferably 600 μm or less, and even more preferably 300 μm or less. The lower limit of the particle size range is not particularly limited, but is preferably 10 μm or more, more preferably 50 μm, and even more preferably 100 μm or more. By setting the upper limit of the particle size range of the wood flour to 1000 μm or less, the compatibility with the resin is improved, and the strength and toughness of the molded product of the wood flour resin composite material tend to be improved. In addition, by setting the lower limit of the particle size range of the wood flour to 10 μm or more, the moldability of the wood flour resin composite material tends to be improved. The above particle size range is not particularly limited, but can be adjusted, for example, by a sieving method. Specifically, for example, wood flour with a particle size range of 1000 μm or less can be obtained by sieving using a filter with a mesh size of 1000 μm, while wood flour with a particle size range of 40 μm to 60 μm can be obtained by passing wood flour through a filter with a mesh size of 60 μm and capturing it with a filter with a mesh size of 40 μm.

[0021] The content of wood flour having a particle size range of 10 μm to 1000 μm is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, particularly preferably 95% by mass or more, and extremely preferably 98% by mass or more, based on the total amount of wood flour. The upper limit is not particularly limited, but may be, for example, 100% by mass.

[0022] The wood can be crushed by any conventional method known in the art, and is not particularly limited. Examples of the method include crushing using a blade or an impact crushing method.

[0023] Wood means lignocellulosic materials derived from plants in general, that is, lignocellulosic materials containing lignin, hemicellulose, and cellulose. Wood is not particularly limited, but examples include maple, white ash, cedar, paulownia, black pine, cypress, and beech. Among these, from the viewpoint of high specific gravity and excellent compounding with resin, it is preferable to use one or more of maple and white ash. These may be used alone or in combination of two or more.

[0024] Steaming refers to a process in which wood flour is brought into contact with steam. Details of steaming are described below.

[0025] In the present embodiment, the ratio of the peak height of acetic acid identified by a total ion chromatogram obtained by gas chromatography mass spectrometry under the following measurement condition Z to the peak height of carbon dioxide identified by the total ion chromatogram is 0.1 or less, preferably 0.05 or less, and more preferably 0.01 or less. The lower limit of the peak height ratio of acetic acid is not particularly limited, and the acetic acid peak may be below the detection limit. The peak height ratio of acetic acid may be, for example, 0.0001 or more, or may be 0.001 or more. <Measurement conditions> [Analyzer] Gas chromatograph mass spectrometer: 7890A / 5975C (Agilent Technologies) Pyrolysis sample introduction device: EGA / PY-3030D (manufactured by Frontier Labs) [Gas chromatograph conditions] Carrier gas: Helium Column: DB-5MS UI (length 20 m, inner diameter 0.18 mm, film thickness 0.18 μm) Thermal desorption temperature: 150°C → 30°C / min → 250°C (Used in combination with cryofocusing to capture volatile components.) Gas chromatograph inlet temperature: 300℃ Split ratio: 1:50 Column tank temperature: The heating conditions are shown in the table below. [Table 1] [Mass spectrometry conditions] Ionization method: Electron ionization method Mass spectrometer interface temperature: 300℃ Scan range: m / z 29-500

[0026] In the present embodiment, the ratio of the peak height of acetic acid identified by the total ion chromatogram to the peak height of carbon dioxide identified by the total ion chromatogram obtained by gas chromatography mass spectrometry under the above measurement conditions is preferably 0.1 or less, more preferably 0.05 or less, and even more preferably 0.01 or less. The lower limit of the ratio of the peak height of acetic acid is not particularly limited, and the acetic acid peak may be below the detection limit. For example, all or at least one of the ratios of the peak height of acetic acid may be 0.0001 or more, or may be 0.001 or more.

[0027] In the present embodiment, the ratio of the peak height of acetic acid, formaldehyde, and acetaldehyde identified by the total ion chromatogram obtained by gas chromatography mass spectrometry under the above measurement conditions to the peak height of carbon dioxide identified by the total ion chromatogram is preferably 0.1 or less, more preferably 0.05 or less, and even more preferably 0.01 or less. The lower limit of the ratio of the peak heights of acetic acid, formaldehyde, and acetaldehyde is not particularly limited, and the peaks of acetic acid, formaldehyde, and acetaldehyde may be below the detection limit. For example, the ratio of the peak heights of acetic acid, formaldehyde, and acetaldehyde may be 0.0001 or more, or 0.001 or more, for all or at least one of them.

[0028] In the present embodiment, the ratio of the peak height of formic acid, acetic acid, formaldehyde, and acetaldehyde identified by the total ion chromatogram obtained by gas chromatography mass spectrometry under the above measurement conditions to the peak height of carbon dioxide identified by the total ion chromatogram is preferably 0.1 or less, more preferably 0.05 or less, and even more preferably 0.01 or less. The lower limit of the ratio of the peak height of each of the formic acid, acetic acid, formaldehyde, and acetaldehyde is not particularly limited, and each of the peaks of the formic acid, acetic acid, formaldehyde, and acetaldehyde may be below the detection limit. For example, the ratio of the peak height of each of the formic acid, acetic acid, formaldehyde, and acetaldehyde may be 0.0001 or more, or 0.001 or more, for all or at least one of them.

[0029] The content of the wood flour to be steamed or cooked is not particularly limited, but may be, for example, 10% by mass or more and 80% by mass or less, 20% by mass or more and 75% by mass or less, 30% by mass or more and 70% by mass or less, 40% by mass or more and 65% by mass or less, or 50% by mass or more and 60% by mass or less, relative to the total amount of the wood flour resin composite.

[0030] From the viewpoint of the environmental friendliness of the wood flour resin composite, the lower limit of the content of the steamed wood flour is preferably 50 mass% relative to the total amount of the wood flour resin composite, and may be 51 mass%, 55 mass%, 60 mass%, or 65 mass%.

[0031] In addition, the upper limit of the content of wood flour to be steamed or cooked is preferably 80 mass% from the viewpoints of the fluidity of the wood flour resin composite and the strength and toughness of molded products of the wood flour resin composite, and may be 75 mass%, 70 mass%, 65 mass%, or 60 mass%.

[0032] 1.2.Resin The resin in the present embodiment is not particularly limited, but is preferably a thermoplastic resin, and a conventionally known resin can be used. The resin is not particularly limited, but examples thereof include olefin resins such as polypropylene and polyethylene, polylactic acid, acrylic resins, polyester resins, and thermoplastic elastomers.

[0033] Among them, the resin of the present embodiment is preferably a biomass resin from the viewpoint of excellent environmental compatibility. Here, the biomass resin means a resin produced using raw materials derived from plants. The biomass resin is not particularly limited, but examples of resins using raw materials derived from plants include biopolyethylene, biopolypropylene, biopolyester, biopolyurethane, and biophenol resin. These may be used alone or in combination of two or more.

[0034] The melting temperature of the resin is preferably 140° C. or higher and 180° C. or lower, and more preferably 150° C. or higher and 170° C. or lower. When the melting temperature of the resin is 180° C. or lower, after compounding with wood flour, the resin can be molded without causing thermal decomposition (discoloration) of the wood flour, and molded products of the wood flour resin composite tend to have excellent strength and toughness.

[0035] The resin of this embodiment has a tensile strength measured under the above-mentioned measurement condition A of preferably 25 MPa or more, more preferably 30 MPa or more, and even more preferably 35 MPa or more. When the resin has a tensile strength of 25 MPa or more, the strength of the molded product of the wood flour resin composite material tends to be even better. The upper limit of the tensile strength is not particularly limited, but may be, for example, 100 MPa or less, or 80 MPa or less.

[0036] The resin of this embodiment has a bending strength measured under the above-mentioned measurement condition B of preferably 30 MPa or more, more preferably 35 MPa or more, and even more preferably 40 MPa or more. When the resin has a bending strength of 30 MPa or more, the strength of the molded product of the wood powder resin composite material tends to be even better. The upper limit of the bending strength is not particularly limited, but may be, for example, 100 MPa or less, or 80 MPa or less.

[0037] The resin content is preferably 20% by mass or more and 45% by mass or less, more preferably 25% by mass or more and 45% by mass or less, and even more preferably 30% by mass or more and 45% by mass or less, based on the total amount of the wood flour resin composite. When the resin content is 20% by mass or more, the strength and toughness of the molded product of the wood flour resin composite tend to be superior, and when the resin content is 45% by mass or less, the environmental compatibility tends to be superior.

[0038] 1.3. Compatibilizers The wood flour resin composite material of the present embodiment may contain a compatibilizer. The compatibilizer is not particularly limited as long as it improves the compatibility between the wood flour and the resin, and examples thereof include acrylic polymers and maleic anhydride polymers. The compatibilizer may be reactive, non-reactive, random polymer, or block polymer. From the viewpoint of further improving environmental compatibility, it is preferable that the compatibilizer is produced using raw materials derived from plants.

[0039] The weight average molecular weight of the compatibilizer is 1.0×10 7 It is preferable that the value is equal to or greater than 1.0×10 8 It is more preferable that the weight average molecular weight of the compatibilizer is 1.0×10 or more. 7 By satisfying the above, the compatibility effect tends to be further enhanced.

[0040] The content of the compatibilizer is preferably 0.1% by mass or more and 10% by mass or less, more preferably 0.5% by mass or more and 5.0% by mass or less, and even more preferably 1.0% by mass or more and 5.0% by mass or less, based on the total amount of the wood flour resin composite. By having the content of the compatibilizer in the above range, the strength and toughness of the molded product of the wood flour resin composite tends to be further improved.

[0041] 1.4.Other Ingredients The wood flour resin composite of the present embodiment may contain other components within the scope of the present invention. The other components are not particularly limited, but may include, for example, surfactants, antioxidants, weather resistance improvers, plasticizers, flame retardants, fillers, antistatic agents, and lubricants. These may be used alone or in combination of two or more.

[0042] 2. Molded products The molded product of this embodiment is obtained by molding the wood powder resin composite material of this embodiment. The molding method will be described later. The thickness of the molded product may be within a suitable range depending on the application. The thickness may be 1.2 mm or less, 1.0 mm or less, or 0.8 mm or less. There is no particular lower limit to the thickness, and the thickness may be 0.4 mm or more, or 0.6 mm or more.

[0043] The uses of the molded products are not particularly limited, but examples thereof include toys, daily necessities, household goods, home appliances, and housings for IT devices. More specifically, the uses are not particularly limited, but examples thereof include educational toys, block toys, childcare products for infants and small children, model toys, hangers, glasses, stationery, watches, storage products, clothes pegs, cosmetic containers, sports goods, buckets, outdoor products, fishing products, automotive products, speakers, and earphones. The shapes of the molded products may be any shapes suitable for the respective uses.

[0044] 3. Manufacturing method of wood powder resin composite material The method for producing a wood flour resin composite of this embodiment includes a steaming process for steaming wood flour to obtain a wood flour to be steamed, a washing process for washing the wood flour to be steamed, and a mixing process for mixing the wood flour to be steamed and cooked that has been through the washing process with a resin to obtain a wood flour resin composite. In the method for producing a wood flour resin composite of this embodiment, it is preferable that the ratio of the peak height of acetic acid identified in the total ion chromatogram obtained by gas chromatography mass spectrometry of the wood flour to be steamed and cooked that has been through the washing process to the peak height of carbon dioxide identified in the total ion chromatogram obtained by gas chromatography mass spectrometry of the wood flour to be steamed and cooked before the washing process is 0.1 or less. It is more preferable that the ratio of the peak height of acetic acid identified in a total ion chromatogram obtained by gas chromatography-mass spectrometry of the steam-cooked wood flour that has been subjected to the washing step to the peak height of carbon dioxide identified in a total ion chromatogram obtained by gas chromatography-mass spectrometry of the steam-cooked wood flour that has been subjected to the washing step is 0.1 or less.

[0045] 3.1. Steaming process The steaming process is a process in which wood flour is steamed to obtain wood flour to be steamed. As the steaming method, a conventionally known method can be used and is not particularly limited, but an example thereof includes placing wood flour in a container that is permeable to water vapor and supplying water vapor thereto from a supply source such as a boiler.

[0046] The water vapor is not particularly limited, but examples thereof include saturated steam and superheated steam. Among these, it is preferable to use superheated steam.

[0047] The steam temperature is preferably 160° C. or higher and 240° C. or lower, more preferably 170° C. or higher and 220° C. or lower, and even more preferably 190° C. or higher and 210° C. or lower. By setting the steam temperature at 160° C. or higher, hemicellulose, lignin, and the like contained in the wood flour can be decomposed to a certain extent, and moldability tends to be more excellent. In addition, by setting the steam temperature at 240° C. or lower, excessive thermal decomposition (burning) can be prevented, and thus odor resistance tends to be more excellent.

[0048] The time for which the steam treatment is carried out is not particularly limited, and may be, for example, from 30 seconds to 1 hour, from 1 minute to 30 minutes, or from 5 minutes to 20 minutes. In order to increase the contact between the wood flour and the steam and promote the reaction, the pressure of the steam may be higher than normal pressure.

[0049] 3.2.Cleaning process The washing step is a step of washing the wood flour to be steamed and cooked with water after the steaming step. The washing method is not particularly limited, but for example, a container is filled with water, and the wood flour to be steamed and cooked is placed in the container and stirred. The water used for washing is not particularly limited, but for example, pure water, deionized water, and distilled water can be mentioned. In addition, the water used in the washing step may contain other components within a range that does not impair the effects of the present invention.

[0050] The ratio of the peak height of acetic acid identified by the total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour after the washing process to the peak height of carbon dioxide identified by the total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour before the washing process is preferably 0.1 or less, more preferably 0.05 or less, and even more preferably 0.01 or less. In addition, the ratio of the peak height of acetic acid identified by the total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour after the washing process to the peak height of carbon dioxide identified by the total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour after the washing process is more preferably 0.1 or less, more preferably 0.05 or less, and particularly preferably 0.01 or less. The lower limit of the ratio of the peak height of acetic acid is not particularly limited, and the peak of acetic acid may be below the detection limit. The ratio of the peak heights of acetic acid may be, for example, 0.0001 or more, or may be 0.001 or more.

[0051] The ratio of the peak height of acetic acid, formaldehyde, and acetaldehyde identified by the total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour after the washing process to the peak height of carbon dioxide identified by the total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour before the washing process is preferably 0.1 or less, more preferably 0.05 or less, and even more preferably 0.01 or less. In addition, the ratio of the peak height of acetic acid, formaldehyde, and acetaldehyde identified by the total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour after the washing process to the peak height of carbon dioxide identified by the total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour after the washing process is more preferably 0.1 or less, even more preferably 0.05 or less, and particularly preferably 0.01 or less. The lower limit of the ratio of the peak heights of the acetic acid, formaldehyde, and acetaldehyde is not particularly limited, and the peaks of the acetic acid, formaldehyde, and acetaldehyde may be below the detection limit. For example, the ratio of the peak heights of the acetic acid, formaldehyde, and acetaldehyde may be 0.0001 or more, or at least one of them may be 0.001 or more.

[0052] The ratio of the peak height of formic acid, acetic acid, formaldehyde, and acetaldehyde identified by the total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour after the washing process to the peak height of carbon dioxide identified by the total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour before the washing process is preferably 0.1 or less, more preferably 0.05 or less, and even more preferably 0.01 or less. In addition, the ratio of the peak height of formic acid, acetic acid, formaldehyde, and acetaldehyde identified by the total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour after the washing process to the peak height of carbon dioxide identified by the total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour after the washing process is more preferably 0.1 or less, more preferably 0.05 or less, and particularly preferably 0.01 or less. The lower limit of the ratio of the peak heights of the formic acid, acetic acid, formaldehyde, and acetaldehyde is not particularly limited, and the peaks of the formic acid, acetic acid, formaldehyde, and acetaldehyde may be below the detection limit. For example, the ratio of the peak heights of the formic acid, acetic acid, formaldehyde, and acetaldehyde may be 0.0001 or more, or at least one of them may be 0.001 or more.

[0053] In the washing step, the temperature of the water used for washing is preferably 0° C. or higher and 60° C. or lower, more preferably 5° C. or higher and 40° C. or lower, and even more preferably 10° C. or higher and 20° C. or lower. When the temperature is 0° C. or higher, the removal of odorous components can be promoted, and odor resistance tends to be excellent. Furthermore, when the steam temperature is 60° C. or lower, it is possible to prevent the components in the wood flour to be steamed and cooked from flowing out more than necessary, and therefore the strength, toughness, and moldability of the molded product of the wood flour resin composite tend to be excellent.

[0054] The washing time is not particularly limited, but may be from 10 minutes to 6 hours, from 20 minutes to 4 hours, or from 30 minutes to 2 hours.

[0055] 3.3.Mixing process The mixing step is a step of obtaining a wood powder resin composite material by mixing the wood flour to be steamed and cooked that has been subjected to the washing step with a resin. As a mixing method, a conventionally known method can be used and is not particularly limited, but for example, a method of melting a resin and mixing it with the wood flour to be steamed and cooking, extruding the fibrous mixture from the holes of a die using a conventionally known granulating extruder, cooling it in a water tank, and cutting it with a pelletizer can be mentioned.

[0056] 4. Manufacturing method of molded products The manufacturing method of the molded product of this embodiment includes a molding step of molding the wood powder resin composite of this embodiment to obtain a molded product. The manufacturing method of the molded product can be a conventionally known method, and is not particularly limited, but examples thereof include extrusion molding, injection molding, and blow molding. Since the wood powder resin composite of this embodiment has excellent moldability while containing wood powder, injection molding is particularly suitable. The injection molding is not particularly limited, but examples thereof include melting the wood powder resin composite, pouring the molten wood powder resin composite into a mold via a screw using a conventionally known injection molding machine, and cooling it.

[0057] The molding temperature in the molding step is preferably 160°C or higher and 180°C or lower, more preferably 165°C or higher and 175°C or lower. A molding temperature of 160°C or higher tends to provide better moldability. A molding temperature of 180°C or lower can suppress thermal decomposition, and the molded product of the wood flour resin composite tends to be better in odor resistance, strength, and toughness. The molding temperature in this embodiment means the temperature at which the wood flour resin composite is heated to a fluid state during molding.

[0058] The mold temperature is preferably 60° C. or higher and 85° C. or lower, and more preferably 65° C. or higher and 80° C. or lower. A mold temperature of 60° C. or higher tends to provide better moldability, and a mold temperature of 85° C. or lower tends to provide better production efficiency. The mold temperature refers to the temperature of the mold into which the wood flour resin composite in a fluid state is poured.

[0059] The method for producing a wood flour resin composite material and the method for producing a molded product of this embodiment may include steps other than the steps described above as long as they do not impair the effects of the present invention. EXAMPLES

[0060] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.

[0061] 1. Preparation of Wood Flour Resin Composites (Examples 1 to 7) First, wood (white ash / maple (provided by Mizuno Corporation)) was crushed using an impact crushing method, and then passed through a filter to ensure uniform particle size. The obtained wood flour was steamed at 200°C for 15 minutes, and then the steamed wood flour was washed by immersing it in water at 15°C in a container for 60 minutes. The washed wood flour to be steamed and cooked was mixed with a resin and a compatibilizer as shown in Table 1, and then extrusion-molded and pelletized to obtain the wood-resin composite materials of Examples 1-7.

[0062] Here, the result of a total ion chromatogram obtained by gas chromatography-mass spectrometry of the wood flour to be steamed and cooked before washing with water in Example 1 is shown in Figure 1. The result of a total ion chromatogram obtained by gas chromatography-mass spectrometry of the wood flour to be steamed and cooked after washing with water in Example 1 is shown in Figure 2. The measurement conditions are the same as the measurement conditions Z described above.

[0063] Comparative Example 1 A wood resin composite material of Comparative Example 1 was obtained by the same procedure as in Example 1, except that the steam-cooked wood flour was not washed with water, i.e., non-steam-cooked wood flour was used. Gas chromatography mass spectrometry was performed on the wood flour used for mixing with the resin under the same conditions as in Example 1. The obtained total ion chromatogram is shown in Figure 2.

[0064] 2. Production of molded products The wood powder resin composite obtained above was molded into a drinking cup by injection molding under conditions of a molding temperature of 170° C. and a mold temperature of 70° C. The obtained molded product had a thickness of 1.2 mm (at the thinnest part).

[0065] 3. Evaluation The odor of the obtained wood-resin composite material and the molded product was evaluated by an odor appraiser who is a skilled person in the art. The evaluation criteria are as follows. The results are shown in Table 1. [Evaluation Criteria] 〇: There is no noticeable odor when using it as a food container. ×: The odor is bothersome when used as a food container.

[0066] [Table 2]

[0067] Details of each component shown in Table 1 are as follows. Bio-PBS: bio-PBS (Mitsubishi Chemical) Compatibilizer: Methacrylic acid alkylate, weight average molecular weight 1.0×10 7 , manufactured by Mitsubishi Chemical Corporation [Industrial Applicability]

[0068] INDUSTRIAL APPLICABILITY The present invention has industrial applicability since it can be widely used for housings of toys, daily necessities, household goods, home appliances, and IT devices.

Claims

1. Steamed wood flour, A resin, The wood flour to be steamed and cooked has a ratio of the peak height of acetic acid identified by a total ion chromatogram obtained by gas chromatography-mass spectrometry to the peak height of carbon dioxide identified by the total ion chromatogram, which is 0.1 or less; Wood powder resin composite.

2. The wood flour to be steamed and cooked has a ratio of the peak height of acetic acid, formaldehyde, and acetaldehyde identified by a total ion chromatogram obtained by gas chromatography-mass spectrometry to the peak height of carbon dioxide identified by the total ion chromatogram, which is 0.1 or less. The wood flour resin composite material according to claim 1.

3. Further comprising a compatibilizer, The wood flour resin composite material according to claim 1.

4. The content of the steamed wood flour is more than 50% by mass with respect to the total amount of the wood flour resin composite. The wood flour resin composite material according to claim 1.

5. The wood powder resin composite material according to claim 1 is molded. Molded product.

6. The thickness is 1.2 mm or less. The molded product according to claim 5.

7. A steaming process in which wood flour is steamed to obtain a steamed wood flour; A washing step of washing the steamed and cooked wood flour; A mixing step of mixing the steamed wood flour that has been subjected to the washing step with a resin to obtain a wood flour resin composite material, The ratio of the peak height of acetic acid identified by a total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour after the washing step to the peak height of carbon dioxide identified by a total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour before the washing step is 0.1 or less. A method for manufacturing wood flour resin composite materials.

8. The ratio of the peak height of acetic acid, formaldehyde, and acetaldehyde identified by a total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour after the washing step to the peak height of carbon dioxide identified by a total ion chromatogram obtained by gas chromatography mass spectrometry of the steam-cooked wood flour before the washing step is 0.1 or less. A method for producing the wood flour resin composite material according to claim 7.

9. A molding step of molding the wood flour resin composite material obtained by the method for producing a wood flour resin composite material according to claim 7 to obtain a molded product. Manufacturing method for molded products.

10. The molding temperature in the molding step is 160° C. or higher and 180° C. or lower. A method for producing the molded product according to claim 9.

11. The mold temperature in the molding step is 60° C. or higher and 85° C. or lower. A method for producing the molded product according to claim 9.

Citation Information

Patent Citations

  • Lignocellulose-containing material and its utilization

    JP2003165844A